Knowledge attitudes and practices of healthcare workers on respirator fit testing and PAPR use at a university medical center - Fatimah Alshahrani; Abba Elgujja; Lulwa Alabdan; Jaser S. Alharbi; Ali A. Rabaan; Ibrahim Alzayid; Mohammed Alasiri; Khalid Faqihi; Samih Alanazi (Scientific Reports)
Abstract Particularly during an epidemic of infectious diseases, worker safety in healthcare depends critically on respirator fit testing and the usage of powered air-purifying respirators (PAPR). Reducing hazards requires ensuring healthcare professionals’ (HCW) knowledge, attitudes, and behaviors as well as their compliance with respiratory protection programs. There is little information on these factors in Saudi Arabian healthcare environments, which calls for targeted research. This study aimed to assess healthcare workers’ (HCW) knowledge, attitudes, and practices (KAP) regarding respirator fit testing and powered air-purifying respirator (PAPR) use at King Saud University Medical City (KSUMC) which is referred to as ‘the medical center’ throughout the paper. Specifically, it sought to identify gaps in policy understanding and training, evaluate compliance and confidence levels, and examine how demographic variables influence these outcomes. A total of 204 HCWs from different departments and hospitals around the medical center participated in cross-sectional research. Structured surveys measuring demographic variables, knowledge, attitudes, training experience, and compliance with fit testing and PAPR use gathered data. While chi-square tests and correlation analysis look at relationships between variables, descriptive statistics compile the demographic traits and survey answers. With SPSS, version 27, all the statistical tests were run with a significance threshold of α = 0.05. With respirator fit testing, the results revealed a high compliance rate—93.4%. Nurses had the best rates of compliance and confidence. However, demonstrating a large knowledge gap, only 6.9% (N-36) of the respondents knew about quantitative fit assessment techniques. Among the 82.2% (N-168) of HCWs who reported PAPR usage training, 48% (of N-168) received consistent instructions. While 14.8% (of N-168) of the respondents reported poor confidence, suggesting room for development, PAPR use was rather high—85.2% (N-204). Significant correlations were found between demographic variables and compliance, training, and confidence levels (p < 0.05). In particular, a negative connection between PAPR usage (r = -0.287, p = 0.01) and confidence in fit testing indicated possible specialized effects. This study highlights the need for thorough and consistent respiratory protection training courses for different HCW profiles. Respiratory protection measures at KSUMC may be strengthened even further by addressing knowledge gaps, increasing hands-on training, and strengthening policy communication to guarantee HCW safety and preparedness.